Solid-state lithium battery composite positive electrode material capable of realizing capacity breakthrough, preparation method and all-solid-state lithium ion battery
By introducing active precursor materials with high ionic conductivity on the positive electrode side of solid-state lithium batteries, the problem of low ionic conductivity of traditional positive electrode materials is solved, and the capacity breakthrough of composite positive electrode materials and the energy density of the battery system is achieved.
Patent Information
- Application Number
- CN202411837139.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The ion conductivity of the positive electrode material of traditional lithium-ion batteries is low, which leads to the inability to build an effective ion transmission path in all-solid lithium batteries, limiting the development of the energy density of the battery system, and the addition of inactive support electrolytes reduces the mass proportion of the active oxide positive electrode material, causing anxiety about battery life capacity.
An active positive electrode side electrolyte material with high ionic conductivity itself and can realize the charge-discharge electrochemical process is developed, by introducing precursor materials during the manufacturing process, avoiding the addition of support electrolytes and contributing additional capacity during the battery charge-discharge process to increase the energy density of the battery system.
Through this method, the discharge specific capacity of the composite positive electrode material is increased by at least 25%, the overall energy density of the battery system is improved, the process is simplified, and the production energy consumption is reduced.
Smart Images

Figure CN119650649A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state battery technology, and specifically relates to a solid-state lithium battery composite positive electrode material and a preparation method and an all-solid-state lithium-ion battery that can achieve a capacity breakthrough. Background Art
[0002] Since the introduction of rechargeable lithium-ion batteries to the consumer market in the early 1990s, they have transformed the global communications sector with the revolution in portable electronics. They are a mature and efficient energy storage technology in terms of energy and power density, service life and design flexibility. At present, the commercial application of lithium-ion batteries has largely solved the energy storage problems facing the world. With the increase in application requirements, batteries with high energy density, stable electrochemical properties, safety and low cost have become the focus of research at this stage. Commercial lithium batteries are generally composed of an organic liquid electrolyte, a positive electrode and a negative electrode. Since most liquid organic electrolytes are flammable, traditional lithium-ion laboratories are at risk of fire or even explosion during overcharging, leakage and heating. In addition, most practical applications of liquid lithium batteries have reached 230 Wh kg −1 , which is very close to its theoretical energy density (300 Wh kg −1 ).
[0003] All-solid-state lithium batteries use non-flammable solid electrolytes and high-voltage cathode materials, and their theoretical energy density can exceed 700 Wh kg −1 , currently reaching 300-400 Wh kg −1 Compared with the lithium anode with high theoretical specific capacity (3860 mAhg -1 ) and silicon anode (4200 mAh g -1 ), the positive electrode materials with low theoretical specific capacity have always been the key to limiting the development of energy density of solid-state battery systems.
[0004] Traditional oxide positive electrode materials (LiCoO2, LiFePO4, NCM111) have low inherent ionic conductivity, and it is impossible to construct an effective ion transmission path on the positive electrode side of the all-solid-state lithium battery. Therefore, it is necessary to add a supporting electrolyte with high ionic conductivity on the positive electrode side to artificially construct an ion transmission channel. However, inactive supporting electrolytes will reduce the mass proportion of active oxide positive electrode materials and thus reduce the energy density of the battery system, causing the public to have capacity anxiety about battery life. Therefore, replacing the inactive supporting electrolyte with an active electrolyte material that has ion conductivity and can perform charge and discharge reactions can solve the capacity anxiety problem of current commercial oxide positive electrode materials to a certain extent.
[0005] In summary, it is particularly important to research and develop an active positive electrode side electrolyte material that has high ionic conductivity and can realize the charge and discharge electrochemical process, a solid-state lithium battery composite positive electrode material that can achieve fast ion conduction by itself to avoid the addition of supporting electrolytes and can contribute its own capacity during the battery discharge process to achieve a breakthrough in the composite positive electrode capacity. Summary of the invention
[0006] In view of this, the purpose of the present invention is to develop a solid-state lithium battery composite positive electrode material that can achieve a breakthrough in capacity. The composite positive electrode material of the present invention introduces a precursor material that has high ionic conductivity and can achieve a reversible charge and discharge process during the manufacturing process, which can contribute additional capacity during the battery charge and discharge process to greatly improve the energy density of the battery system.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: On one hand, the present invention provides a method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity, comprising: S1, grinding anhydrous lithium hydroxide and anhydrous ferric chloride in an inert atmosphere to obtain a mixed powder; S2, subjecting the powder to low-temperature heating treatment in the inert atmosphere to obtain a positive electrode precursor material; S3, subjecting a commercial carbon-coated lithium iron phosphate positive electrode material (C@LiFePO4), a precursor material and a conductive additive to mechanical ball milling in a certain proportion in the inert atmosphere to obtain a solid-state battery composite positive electrode material; The specific implementation plan is as follows: (1) Under the protection of an inert atmosphere, the lithium hydroxide and ferric chloride materials are ground and mixed uniformly to obtain a mixed powder; The molar ratio of the lithium hydroxide and ferric chloride is 1-2:1, preferably 1-1.5:1, more preferably 1.2-1.5:1; (2) Under the protection of an inert atmosphere, heating the mixed powder to obtain a positive electrode precursor material; The heating treatment temperature is 40-120°C, preferably 50-80°C, more preferably 60-70°C, and the treatment time is 1-24h, preferably 1-16h, more preferably 12-14h; (3) Under the protection of an inert atmosphere, the positive electrode material, the positive electrode precursor material and the conductive additive are mechanically ball-milled to obtain a solid-state battery composite positive electrode material.
[0008] Furthermore, the lithium hydroxide and ferric chloride are both anhydrous materials; The inert atmosphere gas is one or more of nitrogen and argon. Preferably, the inert atmosphere is high-purity argon gas, the purity of which is greater than 99.99%, and the contents of oxygen and water are respectively less than 0.1 ppm.
[0009] Furthermore, the lithium hydroxide and ferric chloride are fully ground, and the container mortar used is a mortar that has been dried; The time for grinding and mixing lithium hydroxide and ferric chloride is 5-30 minutes, preferably 15-20 minutes; Before the mechanical ball milling, the ball milling jar and the ball milling beads are dried in an oven, and then materials are added to perform sealed ball milling operations.
[0010] Furthermore, the ball milling beads for the mechanical ball milling mixing include two or more types of ball milling beads with different diameters, and the rotation speed of the mechanical ball milling mixing is 100-500 rpm, preferably 200-300 rpm.
[0011] Furthermore, when two types of ball milling beads with different diameters are used, the ball milling beads include two types of diameters of 8-10 mm and 4-5 mm, and the mass ratio of the ball milling beads is 1-5:1, preferably the mass ratio is 1-3:1, and more preferably 2-2.5:1.
[0012] Furthermore, the mechanical ball milling mixing procedure includes forward rotation, intermittent, reverse rotation, and intermittent, and the cycle operation is performed in this synthesis order; the time of each cycle operation is 1 to 9 hours, preferably 6 to 9 hours, and more preferably 8-9 hours; the number of cycles is 1 to 18 times, preferably 6 to 18 times, and more preferably 15-18 times.
[0013] Furthermore, the positive electrode material is a carbon-coated lithium iron phosphate (C@LiFePO4) material, and the carbon content is 1-10wt.%, preferably 1-5wt.%, and more preferably 2-3wt.%; The conductive additive is one or more of acetylene black, activated carbon, carbon nanotubes, graphene, carbon nanofibers, BP2000, KB600, KB300, XC-72, and SuperP.
[0014] Furthermore, the mass ratio of the composite positive electrode material is carbon-coated lithium iron phosphate material: precursor: conductive additive = 40~70:57~27:3, preferably 50~70:47~27:3, more preferably 65-68:32-37:3.
[0015] Furthermore, the preparation method prepares a composite positive electrode material.
[0016] Furthermore, an all-solid-state lithium-ion battery is provided, with a lithium sheet as the negative electrode, lithium phosphorus sulfur chloride (Li6PS5Cl) and lithium zirconium chloride (Li2ZrCl6, CN202010972122.2) as the solid electrolyte layer, and the composite positive electrode material prepared by the preparation method as the positive electrode material.
[0017] The beneficial effects of the present invention are: The preparation process of the composite positive electrode material prepared by the present invention is simple, and the desired product can be obtained by simple hand grinding, low temperature treatment and ball milling mixing method; the raw material price is low, and it is expected to be applied on a large scale; The precursor material prepared by the present invention has high electrical conductivity itself, and can carry out normal battery charging and discharging process without adding supporting electrolyte, thereby avoiding the addition of inactive supporting electrolyte. Therefore, the prepared composite positive electrode material can increase its discharge specific capacity by at least 25% compared with traditional composite positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A flow chart of a method for preparing a composite positive electrode material; Figure 2 The X-ray diffraction pattern of the precursor material prepared in Example 1; Figure 3 X-ray diffraction pattern of the precursor material prepared for Comparative Example 1; Figure 4 X-ray diffraction pattern of the precursor material prepared for Comparative Example 2; Figure 5 EIS spectra of the precursor materials prepared for Example 1, Comparative Example 1 and Comparative Example 2; Figure 6 The EIS spectrum of the precursor material prepared in Comparative Example 3; Figure 7 EIS spectra of the precursor materials prepared for Comparative Examples 5 and 6; Figure 8 EIS spectra of the precursor materials prepared for Comparative Examples 7, 8, and 9; Fig. 9 Electrochemical performance curves of composite cathode materials prepared in Example 2 and Comparative Example 3 in solid-state lithium batteries; Fig.10 The cycle performance diagram of the composite positive electrode material prepared in Example 2 and Comparative Example 3 in a solid-state lithium battery. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.
[0020] The present invention can significantly increase the battery charge and discharge capacity by adding a composite positive electrode material with ion conductivity and electrochemical reaction precursor preparation. Based on manual grinding and low temperature treatment methods, the lithium content can be further controlled to make the precursor material have an ion conductivity of 5 mS cm at room temperature. -1 The composite cathode material prepared by mixing the above precursor materials with commercial carbon-coated lithium iron phosphate cathode materials is used in solid-state lithium batteries, which can avoid the addition of inactive supporting electrolytes, increase the proportion of active substances in the composite cathode material, achieve a breakthrough in the discharge capacity of the composite cathode material, and improve the overall energy density of the battery system.
[0021] Based on the above findings, the first embodiment of the present invention provides a method for preparing a solid-state lithium battery composite positive electrode material that can achieve a breakthrough in capacity. Figure 1 , including: S1, grinding anhydrous lithium hydroxide and anhydrous ferric chloride in an inert atmosphere to obtain a mixed powder; S2, low-temperature heating the powder in the inert atmosphere to obtain a precursor; S3, ball-milling the precursor material and a commercial carbon-coated lithium iron phosphate positive electrode material conductive additive in the inert atmosphere to obtain a composite positive electrode material.
[0022] Preferably, the raw materials in S1 are lithium hydroxide (LiOH, anhydrous grade, 99.9%) and ferric chloride (FeCl3, anhydrous grade, 99.9%).
[0023] Preferably, the optimal time for manual grinding in S1 is 30 minutes, until the white powder of LiOH is evenly distributed.
[0024] Preferably, the molar ratio of the raw materials is LiOH:FeCl3=1.2:1, and the corresponding amounts are LiOH (0.1505g) and FeCl3 (0.8495g). In this formulation, the room temperature ion conductivity of the obtained precursor material is the best.
[0025] Preferably, the optimal temperature for low temperature treatment in S2 is 60°C and the treatment time is 12h; The specific steps of mechanical ball milling are as follows: C@LiFePO4:precursor:conductive additive = 65:32:3 weight ratio is added to the ball mill in the glove box, and the ball mill is strictly sealed in the glove box. Then the ball mill is placed in the ball mill and fixed, and the ball mill is set to work in a 5-minute forward rotation, 10-minute interval; 5-minute reverse rotation, 10-minute interval mode, and the speed is set at 200 rpm. After the ball milling process is completed, the composite positive electrode material can be prepared.
[0026] Based on the above embodiment, the stoichiometric ratio of lithium hydroxide and ferric chloride is 1-2:1.
[0027] On the basis of the above embodiment, the ball milling beads synthesized by mechanical ball milling include at least two types of diameters, and the rotation speed of the mechanical ball milling synthesis is 100-500 rpm, and the time is 1-48 hours.
[0028] Based on the above embodiment, the mechanical ball milling synthesis procedure includes forward rotation, intermittent, reverse rotation, and intermittent, and the cycle operation is performed in this order.
[0029] Based on the above embodiment, the zirconium dioxide ball milling beads include two types of diameters, 10 mm and 5 mm, and the mass ratio of the ball milling beads is 2-5:1.
[0030] Based on the above embodiment, the inert atmosphere is high-purity argon gas, the purity of the high-purity argon gas is ≥99.999%, and the oxygen and water contents are less than 0.01 ppm.
[0031] High-purity argon has the function of protecting the inert atmosphere in the glove box. The oxygen and water content is less than 0.01ppm, which can reduce the influence of moisture absorption on the electrochemical properties of the material.
[0032] On the basis of the above embodiment, the conductive additive is one of carbon nanotubes, graphene, carbon nanofibers, BP2000, KB600, KB300, XC-72, SuperP, acetylene black, and activated carbon. Adding the conductive additive is to construct an electron transport network inside the positive electrode material to reduce the polarization problem caused by the low electronic conductivity of the positive electrode material.
[0033] On the basis of the above embodiment, the process further includes drying the ball mill jar and the ball mill beads in an oven before the mechanical ball milling synthesis, and then adding materials and sealing.
[0034] Before mechanical ball milling, the ball mill and ball milling beads need to be dried in a 60°C oven for 12 hours to fully remove a small amount of moisture on the ball mill and ball milling beads, and then the material addition operation is carried out, followed by mechanical ball milling synthesis. The moisture on the ball mill and ball milling beads will cause the raw materials and final products to absorb moisture, causing the material to undergo hydrolysis reaction, and ultimately affecting its product state.
[0035] The solid-state lithium battery composite positive electrode material prepared by the method of manual grinding, low temperature treatment and mechanical mixing in the present invention has a very high active material ratio, avoids the addition of supporting electrolyte, and improves the energy density of the battery system. In addition, the composite positive electrode material prepared by the above method does not require high temperature treatment, the process is simple, and the production energy consumption is reduced.
[0036] The present invention is described in detail with reference to the following specific embodiments.
[0037] The equipment for precursor material ion conductivity and solid-state full battery testing and assembly includes ordinary cylindrical mold (Φ10mm), solid-state battery test mold (Φ10mm), manual tablet press, multi-channel electrochemical workstation, battery detection system. The solid-state full battery assembly process is used in a dry inert atmosphere (high-purity argon) glove box, in which the oxygen and water content are both below 0.1ppm.
[0038] Example 1
[0039] In a dry high-purity argon (oxygen and water contents are both below 0.1 ppm) glove box, 0.1505 g of lithium hydroxide and 0.8495 g of ferric chloride (the molar ratio of LiOH:FeCl3 added is 1.2:1) are weighed and manually ground in an agate mortar for 30 minutes. The ground material is then heated to 60°C in the glove box and maintained for 12 hours to obtain a precursor material.
[0040] The agate mortar was dried in an oven at 60°C for 12 hours before use; Example 2
[0041] In a dry high-purity argon (wherein the oxygen and water contents are both below 0.1ppm) glove box, C@LiFePO4 (carbon content of about 2 wt.%) from Shanghai Aladdin Biochemical Technology Co., Ltd, the precursor material prepared in Example 1 and the conductive additive KB600 were added into a ball mill at a weight ratio of 65:32:3, and the ball mill was strictly sealed in the glove box, and the ball mill was set to work in a 5-minute forward rotation, 10-minute interval; 5-minute reverse rotation, 10-minute interval mode, and the speed was set at 200 rpm. The operation time for each cycle was 9 hours; the number of cycles was set to 18 times. After the ball milling program was completed, the composite positive electrode material could be prepared.
[0042] Before mechanical ball milling, the ball mill jar and ball milling beads need to be dried in a 60°C oven for 12 hours; The ball milling beads include two types of diameters: 10 mm and 5 mm, and the mass ratio of the ball milling beads is 2:1.
[0043] Comparative Example 1 The process and conditions are the same as those in Example 1, except that the molar ratio of LiOH:FeCl3 added in the prepared precursor material is 0.8:1 (the amount of ferric chloride used is 0.8495 g).
[0044] Comparative Example 2 The process and conditions are the same as those in Example 1, except that the molar ratio of LiOH:FeCl3 added to the prepared precursor material is 3:1 (the amount of ferric chloride used is 0.8495 g).
[0045] Comparative Example 3 The process and conditions are the same as those in Example 1, except that the raw materials are replaced with LiCl and Fe(OH)3, and the molar ratio of the added amounts in the prepared precursor material is 1.2:1.
[0046] Comparative Example 4 The process and conditions are the same as those in Example 2, except that lithium zirconium chloride is used instead of the precursor material, and the molar ratio of C@LiFePO4, Li2ZrCl6 and conductive additive added to the prepared composite positive electrode material is 65:32:3.
[0047] Comparative Example 5 The process and conditions are the same as those in Example 1, except that all the precursor raw materials are replaced with LiOH in an amount of 0.1505 g.
[0048] Comparative Example 6 The process and conditions are the same as those in Example 1, except that all the precursor raw materials are replaced with FeCl3 in an amount of 0.8495 g.
[0049] Comparative Example 7 The process and conditions are the same as those in Example 1, except that the prepared precursor raw materials are LiOH and FeCl2, and the molar ratio of LiOH:FeCl2 added is 0.8:1 (the amount of ferrous chloride used is 0.8495 g).
[0050] Comparative Example 8 The process and conditions are the same as those in Example 1, except that the prepared precursor raw materials are LiOH and FeCl2, and the molar ratio of LiOH:FeCl2 added is 1.2:1 (the amount of ferrous chloride used is 0.8495 g).
[0051] Comparative Example 9 The process and conditions are the same as those in Example 1, except that the prepared precursor raw materials are LiOH and FeCl2, and the molar ratio of LiOH:FeCl2 added is 3:1 (the amount of ferrous chloride used is 0.8495 g).
[0052] Figure 2The X-ray diffraction images of Example 1 and Comparative Examples 1 and 2. The horizontal axis of the X-ray diffraction spectrum is the diffraction angle 2θ, and the vertical axis is the diffraction intensity. It can be obtained that the diffraction peak of the lithium chloride crystal phase only appears in the diffraction range of the material of Example 1; while the diffraction peak of the raw material ferric chloride appears in the sample of Comparative Example 1, and the diffraction peak of hydrated lithium chloride appears in the sample of Comparative Example 2, indicating that the material of Example 1 has a reasonable reaction degree and can prepare an ideal reaction product.
[0053] Preparation and testing of material sheets of Example 1 and Comparative Examples 1, 2, and 3 100 mg of the materials obtained in Example 1 and Comparative Examples 1, 2, and 3 were added to a common hollow cylindrical mold (inner diameter Φ10 mm), and a manual tablet press was used to apply a pressure of 500 MPa, and the cold pressing was maintained for 1 minute. Subsequently, the ion conductivity was tested using a Biologic multi-channel electrochemical workstation, in which the test frequency was 7 MHz to 1 Hz and the applied bias was 100 mV.
[0054] Figure 5 The electrochemical impedance spectroscopy of the precursor materials of Example 1 and Comparative Examples 1 and 2 of the present invention is shown in Figure 1. The horizontal axis is the real impedance and the vertical axis is the imaginary impedance. It can be confirmed that the conductivity of Example 1 at room temperature is 5 mS cm -1 , which is significantly higher than the conductivity of comparative example 1 (0.6 mS cm -1 The conductivity of Comparative Example 2 is 0.2 mS cm -1 , indicating that the ion conductivity of the sample in Example 1 is stronger and is at the same level as the currently advanced inactive solid supporting electrolyte. It can replace the inactive supporting electrolyte under the same conditions to ensure the ion conductivity in the composite positive electrode material. Figure 6 This is the electrochemical impedance spectroscopy of the precursor material of comparative example 3 of the present invention. The results can confirm that the ion conductivity of the synthesized material in this comparative example is about 0, and it cannot have normal ion conductivity, so it cannot be used as an active material with ion conductivity. In addition, Figure 7 and Figure 8 The precursor materials prepared in Comparative Examples 5, 6, 7, 8, and 9 are similar to Comparative Example 3, and their ion conductivity is about 0. Normal ion conduction cannot be achieved in the composite positive electrode, and therefore cannot be used as precursor materials that can achieve capacity breakthroughs.
[0055] Assembly and testing of solid-state full batteries based on composite cathode materials 50 mg of Li2ZrCl6 solid electrolyte was added to a hollow cylindrical mold (inner diameter Φ10mm) battery core, 50MPa pressure was applied, and cold pressing was maintained for 1 minute; then 50 mg of Li6PS5Cl solid electrolyte was added to the battery core, 100MPa pressure was applied, and cold pressing was maintained for 1 minute; subsequently, 3 mg of the composite positive electrode material prepared by the above process was added to one side of the lithium zirconium chloride electrolyte, 500MPa pressure was applied, and cold pressing was maintained for 1 minute; lithium sheets were added to one side of the lithium phosphorus sulfur chlorine electrolyte sheet, and aluminum foil and copper foil were added to the positive and negative electrode sides respectively. After assembling the battery, the battery mold was kept under 100MPa pressure and electrochemical testing was performed using a blue battery tester. In this test, the applied current density was 0.1mA cm -2 .
[0056] Fig. 9 and Fig.10 The electrochemical performance curves and cycle performance diagrams of solid-state full batteries based on composite positive electrode materials provided in Example 2 and Comparative Example 3 of the present invention. The specific capacity of the composite positive electrode material in Example 2 can reach 190 mAh g -1 LFP This indicates that the cathode precursor can not only conduct ions during the battery charging and discharging process, but also provide an additional capacity of about 40 mAhg -1 LFP Among them, the positive electrode material obtained in Comparative Example 3 only has C@LiFePO4 as the active material for charge and discharge, so the specific capacity of the composite positive electrode material is 150 mAh g -1 LFP Based on the above results, the discharge capacity of Example 2 is more than 25% higher than that of Comparative Example 4.
[0057] In addition, both of the above two composite cathode materials can undergo a stable electrochemical cycle process and have commercial application prospects. In summary, it can be concluded that the composite cathode material prepared in Example 1 has a higher capacity and energy density.
[0058] The method provided by the present invention has low raw material cost and simple process. The prepared active precursor material has high ionic conductivity and can contribute its own capacity, so as to achieve a capacity breakthrough of solid-state lithium battery composite positive electrode materials and improve the energy density of the battery system.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity, characterized in that: The steps include: (1) Under the protection of an inert atmosphere, grinding and mixing lithium hydroxide and ferric chloride to obtain a mixed powder; The molar ratio of the lithium hydroxide and ferric chloride is 1-2:1; (2) Under the protection of an inert atmosphere, heating the mixed powder to obtain a positive electrode precursor material; The heating treatment temperature is 40-120°C and the treatment time is 1-24h; (3) Under the protection of an inert atmosphere, the positive electrode material, the positive electrode precursor material and the conductive additive are mechanically ball-milled to obtain a solid-state battery composite positive electrode material.
2. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a capacity breakthrough according to claim 1, characterized in that: The lithium hydroxide and ferric chloride are both anhydrous materials; The inert atmosphere gas is one or more of nitrogen and argon, the purity of the argon is greater than 99.99%, and the contents of oxygen and water are respectively less than 0.1 ppm.
3. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity according to claim 1, characterized in that: Grind lithium hydroxide and ferric chloride thoroughly, and use a mortar that has been dried; The time for grinding and mixing lithium hydroxide and ferric chloride is 5-30 minutes; Before the mechanical ball milling, the ball milling jar and the ball milling beads are dried in an oven, and then materials are added to perform sealed ball milling operations.
4. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity according to claim 1, characterized in that: The ball milling beads for the mechanical ball milling mixture include two or more types of ball milling beads with different diameters, and the rotation speed of the mechanical ball milling mixture is 100-500 rpm.
5. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a capacity breakthrough according to claim 4, characterized in that: When two types of ball milling beads with different diameters are used, the ball milling beads include two types of diameters of 8-10 mm and 4-5 mm, and the mass ratio of the ball milling beads is 1-5:
1.
6. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity according to claim 1, characterized in that: The mechanical ball milling mixing procedure includes forward rotation, intermittent, reverse rotation, and intermittent, and the cycle operation is performed in this synthesis order; the time of each cycle operation is 1 to 9 hours; and the number of cycles is 1 to 18 times.
7. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity according to claim 1, characterized in that: The positive electrode material is a carbon-coated lithium iron phosphate material with a carbon content of 1-10 wt.%; The conductive additive is one or more of acetylene black, activated carbon, carbon nanotubes, graphene, carbon nanofibers, BP2000, KB600, KB300, XC-72, and SuperP.
8. The method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a breakthrough in capacity according to claim 1, characterized in that: The mass ratio of the composite positive electrode material is carbon-coated lithium iron phosphate material: precursor: conductive additive = 40~70:57~27:
3.
9. A composite positive electrode material prepared by the method for preparing a solid-state lithium battery composite positive electrode material capable of achieving a capacity breakthrough as claimed in any one of claims 1 to 8.
10. An all-solid-state lithium-ion battery, characterized in that: A lithium sheet is used as the negative electrode, lithium phosphorus sulfur chlorine and lithium zirconium chloride are used as the solid electrolyte layer, and a composite positive electrode material prepared by the preparation method according to any one of claims 1 to 8 is used as the positive electrode material.
Citation Information
Patent Citations
Preparation method and application of lithium zirconium chloride
CN112062154A
Preparation method of positive electrode composite material for high energy density all-solid-state lithium ion battery
CN110085835A
Positive active material, preparation method thereof and electrochemical energy storage device
CN110957474A
Method for preparing lithium battery positive electrode material LiFePO4 / C with high activity and high electrical property
CN117003216A